2007
DOI: 10.1007/s00467-007-0567-2
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-resistant nephrotic syndrome: long-term evolution after sequential therapy

Abstract: We present a retrospective study of 30 children of mean age 3.02 +/- 1.81 years with steroid-resistant nephrotic syndrome (SRNS) treated with intravenous injection of methylprednisolone plus orally administered prednisone; 24 children also received cyclophosphamide (CP). Sixteen were resistant to steroids from the beginning, and 14 after a mean of 11.26 +/- 16.61 months. The initial histological diagnosis was: 18 minimal change disease (MCD), 11 focal segmental glomerulosclerosis (FSGS) and one diffuse mesangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 44 publications
0
11
1
3
Order By: Relevance
“…CsA treated children achieved a 41.7% remission rate at 6 months, this was 36.4% and 19.1% in MMF and TAC group. This was much lower than reported in previous studies (12,13,(20)(21)(22), they all reported a 6 months' remission rate of over 50%. Whether the significant difference and doses of concomitant steroids led to this result deserves further study.…”
Section: Discussioncontrasting
confidence: 68%
“…CsA treated children achieved a 41.7% remission rate at 6 months, this was 36.4% and 19.1% in MMF and TAC group. This was much lower than reported in previous studies (12,13,(20)(21)(22), they all reported a 6 months' remission rate of over 50%. Whether the significant difference and doses of concomitant steroids led to this result deserves further study.…”
Section: Discussioncontrasting
confidence: 68%
“…Studies shown glucocorticoid remains the mainstay of childhood NS treatment. There are many factors induced to modulate NS response to drug intervention such as the expression of P-gp, a product of MDR-1 [18,19]. In the kidney, the P-gp is expressed in the brush border membrane of proximal tubular epithelial cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MMF has little effect on other cells and is unlikely to cause severe adverse reactions such as bone marrow suppression. This drug has recently been used to treat nephrotic syndrome in adults and children [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. However, in reviewing the literature, we were unable to determine the benefits of MMF treatment in children with SRINS, especially those <2 years.…”
Section: Introductionmentioning
confidence: 85%